2014
DOI: 10.5586/asbp.2014.014
|View full text |Cite
|
Sign up to set email alerts
|

Alisma plantago-aquatica L.: the cytoskeleton of the suspensor development

Abstract: The actin and the tubulin cytoskeleton organization during the differentiation of the embryo-suspensor in Alisma plantago-aquatica was studied in comparison with the development of embryo, using immunofluorescence detection and rhodamine-phalloidin assay. At the early stage of the suspensor basal cell development (from 2-to ~10-celled embryos) microfilaments form an abundant network in the cytoplasm of the basal cell, while the microtubules form a delicate network. At the mature stage of development (from a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…A vast number of studies confirm the relationship between high ploidy of nuclei and the volume of the suspensor equipped with transfer walls and involved in the absorption of nutrients from the endosperm. A similar correlation was also observed in endosperm, in which highly polyploid nuclei are usually at the chalazal pole, in the place where many wall ingrowths are engaged in the absorption of nutrients from seed integuments (Brady 1973; Bohdanowicz 1997; Łuszczek et al 2000; Kozieradzka-Kiszkurno et al 2002, 2007; Kozieradzka-Kiszkurno and Bohdanowicz 2003; Świerczyńska and Bohdanowicz 2014; Henry and Goldberg 2015). In the four-celled suspensor of P. sativum , wall ingrowths are present on its whole surface, which maintains contact with the endosperm (Marinos 1970a, b).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…A vast number of studies confirm the relationship between high ploidy of nuclei and the volume of the suspensor equipped with transfer walls and involved in the absorption of nutrients from the endosperm. A similar correlation was also observed in endosperm, in which highly polyploid nuclei are usually at the chalazal pole, in the place where many wall ingrowths are engaged in the absorption of nutrients from seed integuments (Brady 1973; Bohdanowicz 1997; Łuszczek et al 2000; Kozieradzka-Kiszkurno et al 2002, 2007; Kozieradzka-Kiszkurno and Bohdanowicz 2003; Świerczyńska and Bohdanowicz 2014; Henry and Goldberg 2015). In the four-celled suspensor of P. sativum , wall ingrowths are present on its whole surface, which maintains contact with the endosperm (Marinos 1970a, b).…”
Section: Discussionsupporting
confidence: 52%
“…An increase in DNA content (via endocycles) may significantly enhance transcription and improve cell metabolism due to gene multiplication (Świerczyńska and Bohdanowicz 2014; Henry and Goldberg 2015). As it was demonstrated in the current study, the increase in DNA content in P. sativum var.…”
Section: Discussionmentioning
confidence: 99%
“…The cytoskeleton plays an important role in many cellular processes, for example cellular signaling, organelle motility and subcellular compartmentation during plant growth and development [55,56]. To date, only a few studies have been reported on the cytoskeleton during the formation, development and differentiation of polyploid cells of embryo-suspensor in: Sedum acre [23], Alisma plantago-aquatica [57] and Gagea lutea (L.) Ker Gawl., [58]. In all of the above species, the authors have shown the presence of an abundant actin and tubulin cytoskeleton in endopolyploid suspensor basal cells.…”
Section: Suspensor Specializationmentioning
confidence: 99%